Malawi Economic Monitor, December 2020 : Doing More with Less - Improving Service Delivery in Energy and Water - World Bank (World Bank, Lilongwe, 2020)
The pandemic has induced a sharp recession in many countries across the globe. The COVID-19 (coronavirus) pandemic has caused an unprecedented shock to the global economy and led to an expected overall contraction of 4.4 percent in 2020. Advanced economies are projected to shrink by 5.8 percent and emerging and developing economies by 3.3 percent. With large uncertainty about wide and affordable access to vaccines, the outlook for 2021 is for a modest recovery of 5.2 percent. Malawi’s economy has been heavily affected, with growth projected at 1.0 percent in 2020, down from earlier projections of 4.8 percent. With population growth around 3.0 percent, this represents a 2.0 percent contraction in per capita GDP. Political stability has returned following the June 2020 Presidential elections, which should support investment. However, global and domestic factors emanating from the pandemic are affecting Malawi’s economy, including: 1) disruption in global value chains and trade and logistics; 2) decrease in tourism; and 3) decrease in remittances. This has combined with social distancing policies and behavior to also reduce domestic demand. Lower international oil prices, on the other hand, have helped reduce the import bill and alleviated fuel and transportation price pressures. Services and industry sectors have been particularly hard hit, leading to a heavier impact in urban areas. The travel and accommodation, tourism, and transport sectors have been substantially affected. Wholesale and retail trade, as well as manufacturing and construction activity declined due to disruptions in sourcing materials and subdued demand. However, favorable weather conditions supported a strongagricultural harvest, particularly for maize, which is supporting growth and food security. Yet, production of key export crops, particularly tobacco, have declined. Poverty reduction in Malawi has stagnated in the last 15 years and is expected to worsen with the pandemic. An estimated 12 percent of the economically active population have experienced job losses due to the crisis. Although this labor market impact is moderate compared to some other countries in the region, this comes after more than 15 years of Malawi’s poverty rate stagnating at high levels. Poverty has declined more slowly in Malawi than the rest of Sub-Saharan Africa. Malawi’s poverty rate based on the 1.90 US Dollars threshold has declined by 3 percentage points from 2004 to 2016, from 73.4 to 70.3 percent. This compares to an 11 percentage point drop for Sub-Saharan Africa, from 53.2 to 42.3 percent. The current account deficit is projected to expand to 19.6 percent of GDP in 2020, up from 17.8 percent in 2019. Exports and imports have been affected by transport disruptions and lockdowns in major trading partners, as well as lower international oil prices. Despite the decline in imports, the drop in key exports, particularly tobacco, is expected to be even greater. Moreover, the downturn in the global economy has also reduced the inflow of remittances by 30 percent for the year through October compared to last year.